Through the eyes of the patients: a qualitative study of diabetes patients’ experiences navigating the healthcare system - AshaRani, P. V.; Kumarasan Roystonn,; Ramu, Madhumitha; Brian Tan, Yeow Wee; Devi, Fiona; Shah, M. Iskander; Wang, Peizhi; Fang, Sum Chee; Subramaniam, Tavintharan; Sing, Lee Eng; Siow Ann, Chong; Subramaniam, Mythily (Frontiers in Endocrinology, 2025)
BackgroundExperience maps of patient journeys offer valuable insights into efficient and cost-effective diabetes care that reflects the needs experienced by the patients. This study describes the diabetes patients’ experience navigating the healthcare system.MethodsA phenomenological approach was adopted together with purposive sampling to achieve the study aim. One to one in-depth interviews were conducted with participants who had Type 2 diabetes (with and without diabetes related complications). A deductive thematic analysis was adopted for the study with data sufficiency achieved at thirteen interviews.FindingsThemes and codes were organized under three main stages: pre-diagnosis (stage 1), diagnosis and treatment (stage 2), and living with diabetes (stage 3). Stage 1 included themes for awareness and choice of care provider for initial care, and showed few care gaps, while stage 2 identified several service gaps and unmet needs. The themes that emerged included acceptance and life-facing diabetes and diabetes disease encounters, with several codes captured under the theme. Stage 3 included a theme for diabetes self-care. The usefulness of apps, good communication by the care team and facilitators of self-care were also mentioned. The major unmet needs perceived by the participant were patient-centeredness and personalized care in primary care settings.ConclusionWhile the current diabetes care system was efficacious, areas for improvement exist, and patients expressed a desire for more patient-centered and personalized care, particularly in primary care settings. These findings offer valuable insights into T2DM management and highlight potential areas for enhancing healthcare delivery.